2007
DOI: 10.1002/joc.1559
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of PRECIS in employing future scenarios in Bangladesh

Abstract: Providing Regional Climates for Impacts Studies (PRECIS) is a regional climate model, which is used for the simulation of regional-scale climatology at high resolution (i.e. 50-km horizontal resolution). The calibration of rainfall and temperature simulated by PRECIS is performed in Bangladesh with the surface observational data from the Bangladesh Meteorological Department (BMD) for the period . The Climate Research Unit (CRU) data is also used for understanding the performance of the model. The results for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 22 publications
(20 reference statements)
3
11
0
Order By: Relevance
“…Model overestimated pre-monsoon rainfall and underestimated monsoon rainfall with amounts in post-monsoon and dry periods is almost closer. The similar result is reported by Islam et al [17]. To find an adjustment between model and observed rainfall amounts the following regression equation is proposed: RF estimated = constant + slope RF scenario (1) where RF estimated is the rainfall to be projected and RF scenario is the PRECIS simulated rainfall scenario.…”
Section: Calibration Of Rainfall In Bangladeshsupporting
confidence: 70%
See 2 more Smart Citations
“…Model overestimated pre-monsoon rainfall and underestimated monsoon rainfall with amounts in post-monsoon and dry periods is almost closer. The similar result is reported by Islam et al [17]. To find an adjustment between model and observed rainfall amounts the following regression equation is proposed: RF estimated = constant + slope RF scenario (1) where RF estimated is the rainfall to be projected and RF scenario is the PRECIS simulated rainfall scenario.…”
Section: Calibration Of Rainfall In Bangladeshsupporting
confidence: 70%
“…TRMM derived rainfall can be considered as the ground-truth amount even it scans from the upper side of the convective systems. The TRMM measured rainfall is already calibrated with ground-based rain-gauge rainfall in Bangladesh (Islam and Uyeda [17]). It is found that TRMM is able to catch about 97% of the surface rain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regional model includes 19 vertical levels from the surface to approximately 30 km in the stratosphere and solves a hydrostatic version of the full primitive equations on a spherical‐polar grid [ Jones et al , 2004]. PRECIS has been successfully applied in previous studies to assess future changes in precipitation and cloud formation in Costa Rica [ Karmalkar et al , 2008], changes in coastal wind strength off the west coast of South America [ Garreaud and Falvey , 2008], extreme events in China [ Zhang et al , 2006] and climate in Bangladesh [ Nazrul Islam et al , 2008].…”
Section: Methodsmentioning
confidence: 99%
“…Almost without exception, these studies show ice-on occurring progressively later in the year and ice-off progressively earlier in the year, resulting in a general decrease in the duration of lake ice cover and a corresponding increase in the duration of the ice-free season. In an analysis of the history of the occurrence of ice cover on eleven Swiss lakes that do not freeze over every winter, HENDRICKS FRANSSEN and SCHERRER (2008) showed that the frequency of occurrence of ice cover has decreased substantially over the past 40 years.…”
Section: Wwwrevhydrocommentioning
confidence: 99%